2002
DOI: 10.1136/bjsm.36.3.173
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided sclerosis of neovessels in painful chronic Achilles tendinosis: pilot study of a new treatment

Abstract: Background: The mechanism that causes pain in chronic Achilles tendinosis is not known. However, high resolution colour Doppler ultrasound has shown that neovascularisation may be involved. Objective: To investigate if sclerosing the neovessels would affect the level of tendon pain. Methods: The effect of colour Doppler ultrasound guided injection of a sclerosing agent, polidocanol, against neovessels was studied in 10 patients (seven men and three women, mean age 55 years) with painful chronic mid-portion Ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
297
3
5

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 350 publications
(317 citation statements)
references
References 38 publications
9
297
3
5
Order By: Relevance
“…One study reports that 89% of the runners with Achilles tendinopathy were men (Kvist, 1991). In a review of several treatment studies, the percentage of men was between 45-86%, with the lower percentages seen in the more recent studies (Nelen et al, 1989, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Alfredson and Öhberg, 2005d.…”
Section: In a Populationmentioning
confidence: 99%
See 4 more Smart Citations
“…One study reports that 89% of the runners with Achilles tendinopathy were men (Kvist, 1991). In a review of several treatment studies, the percentage of men was between 45-86%, with the lower percentages seen in the more recent studies (Nelen et al, 1989, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Alfredson and Öhberg, 2005d.…”
Section: In a Populationmentioning
confidence: 99%
“…When studying Achilles tendon injuries in athletes, Kvist (1991) found that the mean age of subjects with Achilles tendon disorders was 28±9 years, while it was 20±8 years in those without these disorders. Treatment studies (both surgical and non-surgical), that not only include athletes, report that the average age of patients with Achilles tendinopathy ranges between 30 and 55 years, with a total range from 17-80 years of age (Nelen et al, 1989, Leach et al, 1992, NiesenVertommen et al, 1992, Schepsis et al, 1994, Alfredson et al, 1998b, Alfredson et al, 1998c, Angermann and Hovgaard, 1999, Paavola et al, 2000a, Paavola et al, 2000b, Mafi et al, 2001, Öhberg and Alfredson, 2002, Paavola et al, 2002b, Neeter et al, 2003, Alfredson and Öhberg, 2005d. In a prospective study, Johansson (1986) reported that the annual incidence of Achilles tendon overuse injury in elite orienteers was 7%.…”
Section: In a Populationmentioning
confidence: 99%
See 3 more Smart Citations